High Frequency of Concomitant Food Allergy Development and Autoantibody Formation in Children Who Have Undergone Liver Transplantation. Issue 11 (November 2019) - Käppi, Timo; Rabe, Hardis; Lingblom, Christine; Hesselmar, Bill; Kullberg-Lindh, Carola; Wold, Agnes E.; Wennerås, Christine; Saalman, Robert
Abstract : Background: Allergy and other immune-mediated diseases are more frequently reported in children who have undergone liver transplantation. Furthermore, autoantibodies are also prevalent, suggesting a state of immune dysregulation in these patients. Whether or not these processes occur simultaneously in the same individual has not been studied previously. Methods: A cohort of 43 children who had undergone liver transplantation for nonautoimmune liver disease at median age of 1.3 years was investigated for allergy and autoimmune disease. Sensitization to food and inhalant allergens was assessed, and autoantibodies were measured. Results: The prevalence of food allergy was 26% and that of respiratory allergy was 23%, whereas 33% and 26% of the subjects were sensitized to food and inhalant allergens, respectively. Autoimmune disease (ie, autoimmune hepatitis) occurred in a single individual (2%), whereas autoantibodies were present in 44% of the children. Food allergy and autoantibodies occurred concomitantly in 19% of the children, which was almost twice the frequency expected by chance (11%, P = 0.04). Respiratory allergy and the presence of autoantibodies were unrelated (12% concurrence versus the expected 10%, P = 0.73). In the logistic regression analysis, autoantibody formation was associated with discontinued immunosuppression and food allergy, with odds ratios of 13 ( P = 0.01) and 7.1 ( P = 0.03), respectively. Conclusions: In contrast to respiratory allergy, food allergy and autoantibody formation occurred together in the same children who underwent liver transplantation at a frequency higher than would be expected by chance. This may reflect an underlying immune dysregulation that impairs immune tolerance to both food allergens and autoantigens. Abstract : Supplemental Digital Content is available in the text.